First Person: The pandemic's silver lining: Real talk for future teachers. (September 2020) - Hipp, Jamie
When the COVID-19 pandemic closed her university campus, Jamie Hipp had to move her popular arts integration class for preservice teachers to a virtual format. She was surprised to learn that her students wanted more than regular sessions during their scheduled class times; they wanted additional opportunities for "real teacher talk" about going on interviews, setting up a classroom, and other practical matters that weren't being covered in their preservice program. Hipp set up a series of virtual sessions on topics of interest to students, in addition to regular class sessions. The sessions went so well that Hipp intends to continue having them, even after the pandemic is over and her campus reopens .